2021
DOI: 10.3390/ijms22031269
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Human Platelet Lysate as an Alternative to Foetal Bovine Serum for In Vitro Expansion of Chondrocytes

Abstract: Osteoarthritis (OA) is a degenerative joint disease that affects a lot of people worldwide. Current treatment for OA mainly focuses on halting or slowing down the disease progress and to improve the patient’s quality of life and functionality. Autologous chondrocyte implantation (ACI) is a new treatment modality with the potential to promote regeneration of worn cartilage. Traditionally, foetal bovine serum (FBS) is used to expand the chondrocytes. However, the use of FBS is not ideal for the expansion of cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 104 publications
0
19
0
Order By: Relevance
“…Cartilage is an avascular and alymphatic tissue. 111 Thus, unlike in other tissue injuries, exosomes are not suitable for infusing intravenously for treating cartilage defects. In fact, all of the included studies administered exosomes directly to the affected joint, as intra-articular administration increases bioavailability and reduces off-target effects, thereby improving the delivery of exosomes to the cartilage and decreasing the dose of exosomes needed.…”
Section: Resultsmentioning
confidence: 99%
“…Cartilage is an avascular and alymphatic tissue. 111 Thus, unlike in other tissue injuries, exosomes are not suitable for infusing intravenously for treating cartilage defects. In fact, all of the included studies administered exosomes directly to the affected joint, as intra-articular administration increases bioavailability and reduces off-target effects, thereby improving the delivery of exosomes to the cartilage and decreasing the dose of exosomes needed.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have confirmed that HAS enhances the proliferation of chondrocytes and PRP boosts the proliferation and redifferentiation of dedifferentiated chondrocytes ( Jeyakumar et al, 2017 ; Jeyakumar et al, 2019 ). The current research on PL supports its application to promote the expansion of chondrocytes; however, there are doubts regarding the regulation of chondrocyte redifferentiation ( Rikkers et al, 2020 ; Liau et al, 2021 ). Recent studies of LMWF5A have shown its potential in inducing fibroblast-like chondrocytes to redifferentiate into functional chondrocytes ( Hausburg et al, 2018 ).…”
Section: Extracellular Microenvironmentmentioning
confidence: 99%
“…This term is mainly to describe the various types of cells (e.g. chondrocytes and MSCs [ 23 , 163 ]), which can develop the property of chondrocytes to form cartilage. This term may also be used to describe tissue engineered constructs to form cartilage.…”
Section: Bioactive Peptide To Promote Chondrogenesismentioning
confidence: 99%